2020
DOI: 10.1177/1360780420965982
|View full text |Cite
|
Sign up to set email alerts
|

Something ‘Old’, Something ‘New’? The UK Space of Political Attitudes After the Brexit Referendum

Abstract: This study focuses on the political attitudes of UK citizens in the aftermath of the ‘Brexit’ vote. It has been argued that differences within electorates across Europe are found in disputes over taxes, redistribution of wealth and social welfare, as much as in divergent ideas on how to deal with globalisation, migration, and climate change. This article uses the 2016–2017 round of the European Social Survey (N = 1959) to shed light on two important issues in regard to the relationship between ‘old’ and ‘new’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…), but a number of authors have shown that a very similar homology actually pertains to the relationship between the social space and the space of political position-taking in various national contexts (see e.g. Harrits et al 2010;De Keere 2018;Jarness et al 2019;Lindell and Ibrahim 2021). These contributions demonstrate that a two-dimensional social space corresponds systematically to twodimensional political spaces, comprising both the "old" politics of life chances and the "new" politics of life choices.…”
Section: Class Voting and Culturementioning
confidence: 94%
“…), but a number of authors have shown that a very similar homology actually pertains to the relationship between the social space and the space of political position-taking in various national contexts (see e.g. Harrits et al 2010;De Keere 2018;Jarness et al 2019;Lindell and Ibrahim 2021). These contributions demonstrate that a two-dimensional social space corresponds systematically to twodimensional political spaces, comprising both the "old" politics of life chances and the "new" politics of life choices.…”
Section: Class Voting and Culturementioning
confidence: 94%